Governance and Regulations : Contemporary Issues. - Marano, Pierpaolo; Grima, Simon (Contemporary studies in economic and financial analysis, 2018)
Volume 99 is a collection of theoretical and empirical studies in governance and regulation, with application to both macro and microeconomic issues.